Ablate and pace revisited: long term survival and predictors of permanent atrial fibrillation. Issue 9 (15th August 2003) - Queiroga, A; Marshall, H J; Clune, M; Gammage, M D
Abstract : Objective: To assess long term mortality and identify factors associated with the development of permanent atrial fibrillation after atrioventricular (AV) node ablation for drug refractory paroxysmal atrial fibrillation. Design: Retrospective cohort study. Setting: UK tertiary centre teaching hospital. Patients: Patients admitted to the University Hospital Birmingham between January 1995 and December 2000. Interventions: AV node ablation and dual chamber mode switching pacing. Main outcome measures: Long term mortality and predictors of permanent atrial fibrillation, assessed through Kaplan-Meier curves and logistic regression. Results: 114 patients (1995–2000) were included: age (mean (SD)), 65 (9) years; 55 (48%) male; left atrial diameter 4 (1) cm; left ventricular end diastolic diameter 5 (1) cm; ejection fraction 54 (17)%. Indications for AV node ablation were paroxysmal atrial fibrillation in 95 (83%) and paroxysmal atrial fibrillation/flutter in 19 (17%). The survival curve showed a low overall mortality after 72 months (10.5%). Fifty two per cent of patients progressed to permanent atrial fibrillation within 72 months. There was no difference in progression to permanency between paroxysmal atrial fibrillation and paroxysmal atrial fibrillation/flutter (log rank 0.06, p = 0.8). Logistic regression did not show any association between the variables collected and the development of permanent atrial fibrillation, although age over 80 years showed a trend (p = 0.07). Conclusions: Ablate and pace is associated with a low overall mortality. No predictors of permanent atrial fibrillation were identified, but 48% of patients were still in sinus rhythm at 72 months. These results support the use of dual chamber pacing for paroxysmal atrial fibrillation patients after ablate and pace.